Understanding service provider behavior in the pre-purchase phase of service encounter in a high contact customer-oriented service system: Using a game-based simulation experiment approach - Red, Rachelle Parentela (Animo Repository, 2012)
Service encounter greatly defines a service experience since this is the period of time during which a customer directly interacts with a service provider. These encounters are most evident in a high contact service system since it involves interactions between a service provider and customer to a great extent. This makes service encounters as an essential part of this kind of service system since it basically breathes through the performances in a service encounter. Also, during these encounters also known as interactions, the customer receives a sort of snapshot of the service provider's level of service provision. Thus, service providers will play an influential role in determining the success of the service since they are the main contact of a customer in a service encounter. Service provider impacts customer perceptions on how well they can serve them. Service may be spotless and delivered on time as ordered but if the customer leaves with a negative impression from the attitude of an employee, then other efforts may be overlooked. Given the importance of the role of the service provider in a service encounter, there have been limited researches done to understand and quantify what factors and conditions allow to utilize service providers at their maximum potential. Often times, the focus is on making sure that the customer gets what they want without regarding the side of the service provider. Thus, this study aims to understand what factors can influence the service providers behavior in a service encounter that would want them to engage customers longer. Behavior in this context would be on how service provider would decide to use effort (prolong the encounter) and hastening (shorten the encounter) actions in handling service encounters. Generally, this research aims to provide a deeper understanding into the role of service provider behavior that governs the interaction between service provider and customers. A game simulation model was developed to capture simultaneous considerations of certain attributes and not just the independent selection. This has provided a different approach in getting mental models which is usually anecdotal or survey based. With this, Selection by Aspects algorithm was adopted to determine the choice polynomials of each decision maker. These choice polynomials described the attributes that were being considered by a service provider in handling service encounters. More analysis was done to get more valuable insights on how the decision making process can influence a service providers behavior. Conclusions on the comparison of perception ranking and actual ranking were also derived in this study which exhibits that surveys are indeed limited in capturing what they think are happening and not what really is happening.